Overview of the Production Results of All Blood Components at UDD PMI Semarang City in 2020 - Rina Puspita (STIE AAS Surakarta, 2021)
All components in the blood have their respective duties and functions that support the work of blood in the body. Blood has many important roles, such as supplying oxygen and nutrients to cells and tissues, helping to get rid of waste or metabolic waste substances to protecting the body from infections and foreign substances that can harm health. This study aims to determine the results of the production of all blood components at UDD PMI Semarang City in January - December 2020, so that the production amount of each type of blood component can be seen. This type of research is a quantitative study with a descriptive research design consisting of one variable of the production of blood components at UDD PMI Semarang City. The research sample used a total sampling of 102,635 samples, the data collection method was in the form of medical record data for UDD PMI Semarang City in the form of the production of blood components from January to December 2020. From 102,635 samples, it was found that the production of Whole Blood (WB) was 6197 kolf/year, Packed Red Cell (PRC) as much as 48802 kolf/year, Thrombocyte Concentrate (TC) as much as 40578 kolf/year, Fresh Frozen Plasma (FFP) as much as 3551 kolf/year, Cryoprecipitate/AHF as much as 396 kolf/year, PRC-Leukodepleted as much as 2518 kolf/year years, and PRC-Leukoreduced as much as 593 kolf/year. In a row, the highest production of blood components at UDD PMI Semarang City in 2020 was PRC 48802 colf/year, TC 40578 colf/year, WB 6197 colf/year, FFP 3551 colf/year, PRC-Leukodepleted 2518 kolf/year, PRC-Leukoreduced 593 colf/year, and AHF396 colf/year.